2014
DOI: 10.15380/2277-5706.jcsr.13.023
|View full text |Cite
|
Sign up to set email alerts
|

Potpourri testicular tumour - combination of seminoma, teratoma and yolk sac tumour of testis in a young adult male

Abstract: Testicular germ cell tumours are the most common malignant tumours seen in adult males in the 20-40 years age group. The cure rate of these tumours is quite high even with the presence of metastasis. But many patients present quite late in the course of the disease, often with complications. We present the case of a young male who presented with mixed germ cell tumour consisting of the unusual combination of seminoma, yolk sac tumour and mature teratoma. Though mixed germ cell tumour is a common entity, presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In one series the most frequent combination of mixed germ cells in the tumours was of teratoma and embryonal carcinoma, the major component being teratomatous embryoid elements with minor foci of yolk sac tumour [8]. Another study reported histologically that nearly 59 % of the mixed germ cell tumours contained seminoma, 41 % yolk sac tumour, and 47 % embryonal carcinoma and teratoma components [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one series the most frequent combination of mixed germ cells in the tumours was of teratoma and embryonal carcinoma, the major component being teratomatous embryoid elements with minor foci of yolk sac tumour [8]. Another study reported histologically that nearly 59 % of the mixed germ cell tumours contained seminoma, 41 % yolk sac tumour, and 47 % embryonal carcinoma and teratoma components [3].…”
Section: Discussionmentioning
confidence: 99%
“…Testicular neoplasia present in a very distinctive age group of distribution and prove higher incidence in the younger male age group of up to15 years old [2]. The majority (~98 %) of testicular tumours are observed to be of the germ-cell origin [3]. Germ cell neoplasia includes the seminomatous (SGCT) and non-seminomatous germ-cell tumour (NSGCT) types.…”
Section: Introductionmentioning
confidence: 99%